Valoración médico legal de las lesiones y su relación con el marco jurídico. - Lalvay Carchi, Diana Carolina (Machala : Universidad Técnica de Machala, 2024)
Introduction: Lesionology is a branch of forensic medicine that is responsible for the study of injuries, which can cause anything from temporary to total disability, causing functional changes, mental alterations, or even death. According to the World Health Organization (WHO) in 2022, it detailed that 12,000 people die due to injuries every day. Ecuador in 2023, with a total of 8,004 events, was the most violent country in Latin America with a homicide rate of 47.25 per 100,000 inhabitants. Objective: Describe the medical-legal assessment of injuries and its relationship with the legal framework through a review of the literature for help in the judicial system. Development: Historically, the assessment of bodily damage began in the year 2,050 BC. In medico-legal terms, injuries correspond to the alteration of the morphology or function of structures, organs, body segments and systems by a third party or an agent. external. Accurate description and recording of injuries guides the cause, the circumstances of their occurrence, or the aggressor. Conclusion: The medico-legal assessment of bodily harm consists of proving with scientific criteria that an injury was caused by a specific event. In Ecuador, the Comprehensive Organic Penal Code regulates penalties for different types of injuries, depending on the severity, the length of disability, which refers to the time necessary for an injury to be repaired, and the organic or functional sequelae they produce.
Introducción: La lesionología es una rama de la medicina forense que se encarga del estudio de las lesiones, las cuales pueden causar desde una incapacidad temporal a una total, provocando cambios funcionales, alteraciones mentales o, incluso, la muerte. Según la Organización Mundial de la Salud (OMS) en 2022, detalló que debido a lesiones mueren 12 000 personas al día. Ecuador en 2023, con un total de 8004 eventos, fue el país en el más violento de América Latina con una tasa de homicidios de 47.25 por cada 100 000 habitantes. Objetivo: Describir la valoración médico legal de las lesiones y su relación con el marco jurídico mediante revisión de la literatura para ayuda en el sistema judicial. Desarrollo: Históricamente la valoración del daño corporal inicia en el año 2.050 antes de Cristo, En términos médico-legales, las lesiones corresponden a la alteración de la morfología o la función de estructuras, órganos, segmentos corporales y sistemas por un tercero o un agente externo. La descripción y el registro precisos de las lesiones orientan a la causa, las circunstancias de su aparición o el agresor. Conclusión: La valoración médico-legal de los daños corporales consiste en probar con criterios científicos que una lesión fue causada por un hecho específico. En Ecuador, el Código Orgánico Integral Penal regula las penas para distintos tipos de lesiones, dependiendo de la gravedad, el tiempo de incapacidad que hace referencia al tiempo necesario para que una lesión se repare, y las secuelas orgánicas o funcionales que produzcan.
Keywords: LESIONES; MEDICO-LEGAL; INCAPACIDAD; RESPONSABILIDAD PENAL